ART AND CRAFT CENTER– أصل الحكاية - محمد نجم (My University, 2025)
This project aims to preserve traditional Palestinian crafts from extinction and revive them as an essential part of the cultural and national identity. The goal is not only to protect the artisanal heritage in the face of ongoing threats from the occupation and its attempts to erase all that is Palestinian, but also to keep it alive and accessible to future generations through education, innovation, community engagement, and by boosting the Palestinian economy through the sale of handicraft products. The concept of the project stems from a deep belief that craftsmanship is not merely a profession, but a narrative of resistance and a living extension of the memory of place and people. Within this complex, I sought to create an environment that integrates production, education, exhibition, and community interaction. The architectural layout is centered around courtyards, open squares, and shaded pathways that reflect the spirit of traditional markets, embodying the idea of a Center for Traditional Arts and Crafts as a vibrant social hub. The building is designed to stand as a testament to Palestinian heritage, drawing inspiration from traditional architecture such as historic homes, while integrating contemporary design elements. The "Origin of the Story" Handicrafts Business Complex is located in Birzeit – Ramallah, an area known for its rich cultural heritage and centuries-old artisanal traditions. The site was carefully chosen for its dynamic connection to the local community and tourists alike, where traditional crafts intersect with everyday life. It is also strategically positioned near the Palestinian Museum, Birzeit University, and the Technology Park, enhancing accessibility and encouraging visitor interaction.